Pengaruh Pajak, Tunneling Incentive, Intangible Asset, Nilai Tukar dan Mekanisme Bonus Terhadap Transfer Pricing - AR, Khorida; Siregar, Indra Gunawan; Rahandri, Daniel; Rohmansyah, Budi; Maulidah, Miyah (Media Akuntansi Perpajakan, 2025)
The purpose of this study is to determine the effect of taxes, tunneling incentives, intangible assets, exchange rates, and bonus mechanisms on transfer pricing of companies listed on the Indonesia Stock Exchange in 2020-2024. This study uses a quantitative approach using secondary data, namely company financial reports. The sample for this study was obtained using a purposive sampling method with sample selection using certain criteria and obtained 10 companies. The analytical method used in this study is panel data regression using eviews 12. The results of this study indicate that taxes affect transfer pricing, while tunneling incentives, intangible assets, exchange rates, and bonus mechanisms do not.